2014
DOI: 10.1097/maj.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interferon Alpha in Endothelial Dysfunction: Insights Into Endothelial Nitric Oxide Synthase–Related Mechanisms

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by the production of autoantibodies against nuclear antigens such as double-stranded DNA. Lupus predominantly affects women (ratio, 9:1). Moreover, premenopausal women with SLE are 50 times more likely to have a myocardial infarction. Although specific risk factors for advanced cardiovascular complications have not been identified in this patient population, endothelial dysfunction is highly prevalent. Recent studies show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…functions [16,17], though the role of innate immune activation in catalyzing HFRS disease symptoms has not been understood. Further, the pathogen recognition receptor(s) (PRR) responsible for recognition and activation of the innate immune response during hantavirus infection of endothelial cells are not well-defined.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…functions [16,17], though the role of innate immune activation in catalyzing HFRS disease symptoms has not been understood. Further, the pathogen recognition receptor(s) (PRR) responsible for recognition and activation of the innate immune response during hantavirus infection of endothelial cells are not well-defined.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…It has been shown that the type I IFN receptor sensitizes macrophages to death caused by L. monocytogenes infection ( 127 ). Interestingly, type I IFN also has been associated with endothelial dysfunction through induction of endothelial nitric oxide synthase ( 128 ). However, the mechanisms of type I IFN-mediated regulation of oxidative stress have not been analyzed in detail.…”
Section: Cytokines and Chemokines With Increased Expression During Sementioning
confidence: 99%
“…It is thought that the common denominator for multiple mechanisms contributing to the development of endothelial dysfunction is diminished activity of endothelial nitric oxide synthase and loss of nitric oxide production. Recent analyses have shown that SLE-specific circulatory factors, TNF-α, interleukin-17, interferons, ligand of cluster of differentiation 40 (CD40L), and C-reactive protein (CRP), lead to endothelial dysfunction via promotion of abnormal eNOS function and enhanced oxidative stress [148]. Among these mediators, type I interferons gained considerable attention.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%